Hallucinogenic drugs in pre-Columbian Mesoamerican cultures - F.J. Carod-Artal (Neurología (English Edition), 2015)
Objectives: The archaeological, ethno-historical and ethnographic evidence of the use of hallucinogenic substances in Mesoamerica is reviewed. Results: Hallucinogenic cactus, plants and mushrooms were used to induce altered states of consciousness in healing rituals and religious ceremonies. The Maya drank balché (a mixture of honey and extracts of Lonchocarpus) in group ceremonies to achieve intoxication. Ritual enemas and other psychoactive substances were also used to induce states of trance. Olmec, Zapotec, Maya and Aztec used peyote, hallucinogenic mushrooms (teonanacatl: Psilocybe spp.) and the seeds of ololiuhqui (Turbina corymbosa), that contain mescaline, psilocybin and lysergic acid amide, respectively. The skin of the toad Bufo spp. contains bufotoxins with hallucinogenic properties, and was used during the Olmec period. Jimson weed (Datura stramonium), wild tobacco (Nicotiana rustica), water lily (Nymphaea ampla) and Salvia divinorum were used for their psychoactive effects. Mushroom stones dating from 3000 BC have been found in ritual contexts in Mesoamerica. Archaeological evidence of peyote use dates back to over 5000 years. Several chroniclers, mainly Fray Bernardino de Sahagún, described their effects in the sixteenth century. Conclusions: The use of psychoactive substances was common in pre-Columbian Mesoamerican societies. Today, local shamans and healers still use them in ritual ceremonies in Mesoamerica. Resumen: Introducción: El continente americano es rico en hongos y plantas psicoactivas, y numero-sas culturas precolombinas mesoamericanas las emplearon con fines mágicos, terapéuticos y religiosos. Objetivos: Se revisan las evidencias arqueológicas, etnohistóricas y etnográficas del uso de sustancias alucinógenas en Mesoamérica. Resultados: Cactus, plantas y hongos alucinógenos se utilizaron para provocar estados altera-dos del nivel de conciencia en ceremonias rituales y curativas. Los mayas ingerían el balché (hidromiel y extracto de Lonchocarpus) en ceremonias grupales para lograr la embriaguez. También emplearon enemas rituales con sustancias psicoactivas para inducir estados de trance. Olmecas, zapotecas, mayas y aztecas usaron el peyote, los hongos alucinógenos (teonanacatl: Psilocybe spp.) y las semillas de ololiuhqui (Turbina corymbosa), que contienen mescalina, psilocibina y amida del ácido lisérgico, respectivamente. La piel del sapo Bufo spp. contiene bufotoxinas, con propiedades alucinógenas y fue usado desde el periodo olmeca. El toloache (Datura estramonio), el tabaco silvestre (Nicotiana rustica), el lirio de agua (Nymphaea ampla) y la hoja de la pastora (Salvia divinorum) se utilizaron por sus efectos psicotropos. Piedra fún-gicas de 3.000 ãnos de antigüedad se han encontrado en contextos rituales en Mesoamérica. Las evidencias arqueológicas del uso del peyote se remontan a más de 5.000 ãnos. Diversos cronistas, entre ellos Fray Bernardino de Sahagún, relataron sus efectos en el siglo xvi. Conclusiones: El empleo de sustancias psicotrópicas fue muy común en las sociedades preco-lombinas mesoamericanas. En la actualidad chamanes y curanderos locales las siguen usando en ceremonias rituales. Keywords: Hallucinogens, Hallucinogenic fungi, Peyote, Pre-Columbian culture, Psilocybe spp., Turbina corymbosa, Palabras clave: Alucinógenos, Culturas precolombinas, Hongos, Peyote, Psilocybe spp., Turbina corymbosa